Motivational Differences Across Post-Acceptance Information System Usage Behaviors: An Investigation in the Business Intelligence Systems Context - Li, Xixi; Hsieh, J. J. Po-An; Rai, Arun (Information Systems Research, 2013)
We identify two post-acceptance information system (IS) usage behaviors related to how employees leverage implemented systems. Routine use (RTN) refers to employees' using IS in a routine and standardized manner to support their work, and innovative use (INV) describes employees' discovering new ways to use IS to support their work. We use motivation theory as the overarching perspective to explain RTN and INV and appropriate the rich intrinsic motivation (RIM) concept from social psychology to propose a conceptualization of RIM toward IS use, which includes intrinsic motivation toward accomplishment (IMap), intrinsic motivation to know (IMkw), and intrinsic motivation to experience stimulation (IMst). We also consider the influence of perceived usefulness (PU)—a representative surrogate construct of extrinsic motivation toward IS use—on RTN and INV. We theorize the relative impacts of the RIM constructs and PU on RTN and INV and the role of personal innovativeness with IT (PIIT) in moderating the RIM constructs' influences on INV. Based on data from 193 employees using a business intelligence system at one of the largest telecom service companies in China, we found (1) PU had a stronger impact on RTN than the RIM constructs, (2) IMkw and IMst each had a stronger impact on INV than either PU or IMap, and (3) PIIT positively moderated the impact of each RIM construct on INV. Our findings provide insights on managing RTN and INV in the post-acceptance stage.